PERSEPSI WISATAWAN SLTP TERHADAP MUSEUM SANG NILA UTAMA PROVINSI RIAU - Muhammad Suhada Putra; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research purposed to know how to perception junior high school student of the museum sang nila utama province Riau. To know that is a driving factor in the self student to visiting the museum sang nila utama province Riau.This research used qualitative descriptive method to analyze to the problems. The sample is the research are 50 sample by using census sampling. And then techniques collected data in this research are using questionnaire, interview, observation, and documentation.Based on the research, the driving factor outside the dominate make a junior high school student to the visit museum sang nila utama province Riau. therefore the lack of appeal of the museum to attract visitors junior high school student.Keywords : Perception, museum sang nila utama, siswa SLTP